UJI EFEKTIVITAS ANTIHIPERGLIKEMIA INFUSA ALGA LAUT COKLAT (Sargassum hystrix) PADA MENCIT JANTAN DENGAN METODE TOLERANSI GLUKOSA - Agung Giri Samudra; Nurfijrin Ramadhani; Cyntia Dwi Utami; Nori Wirahmi; Fathnur Sani K (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
One type of metabolic disease that is always experiencing an increase in sufferers every year in countries around the world is diabetes mellitus. Sargassum hystrix marine algae are the types that are found and quite abundant in Indonesia. This study aims to prove the hypoglycemic effect of Sargassum hystrix infusion in male white mice. The study was conducted using the oral glucose test method in the positive control group (I) given glibenclamide 0.52mg / 20gramBB; group (II) is a negative control given CMC Na 0.5%; group (III) infusion of Sargassum hystrix with a concentration of 2.5% with a volume of 0.2 mL / 20gram BW; group (IV) infusion of Sargassum hystrix with a concentration of 5% by volume of 0.2 mL / 20gram BW. The results were analyzed using One Way Anova which was then followed by Duncan's test. The results showed that Sargassum hystrix infusion had an antihyperglycemic effect (p <0.05) when compared with negative controls. Sargassum hystrix 5% infusion is the best dose with the antihyperglycemic effect statistically the same as the antihyperglycemic effect of glibenclamide.